Computational Models for Auditory Speech Processing - Deng, Li (Computational Models of Speech Pattern Processing, (NATO ASI Series), 1999)
Auditory processing of speech is an important stage in the closed-loop human speech communication system. A computational auditory model for temporal processing of speech is described with details of numerical solution and of the temporal information extraction method given. The model is used to process ﬂuent speech utterances and is applied to phonetic classiﬁcation using both clean and noisy speech materials. The need for integrating auditory speech processing and phonetic modeling components in machine speech recognizer design is discussed within a proposed computational framework of speech recognition motivated by the closed-loop speech chain model for integrated human speech production and perception behaviors.